Consumer Attitude towards Dairy Products – An Empirical Study in Erode District - N.Santhamani; Dr. P.S.Selva Tharangini (International Journal of Engineering and Management Research, 2021)
The dairy industry is one of the most important components of the world food system, and is undergoing dramatic change at the current time. It is highly probable that within ten years, the global dairy industry will be scarcely recognizable from its current form. So, attitudinal changes of consumers also vary in the past 2 decades. Attitude of the consumers will continuously change owing to the technological research and innovation in the dairy industry. So, this research emerged and aimed to examine the consumer attitude towards dairy products in Erode district of Tamilnadu, India. Because Erode district shows its more involvement in agriculture along with dairy products. The researcher has selected 132 consumers who have using the dairy products in different way of usage like milk, butter, butter milk, ghee, palkova, etc. The changes in their attitude would find from a structured questionnaire which consists of demographic and usage of dairy products, and their attitude on dairy products. The collected data were subdued into tables and charts with the help of MS-excel and SPSS 22.0. This research has found the results as most of the respondents were urban area consumers of dairy products, purchasing frequently Aavin products and they were using dairy products for 5 to 10 years in the study area.